Upaya Penggerak Swadaya Masyarakat Dalam Meningkatkan Partisipasi Masyarakat Di Kegiatan Bulan Bhakti Gotong Royong Masyarakat - Mubarok, Abdul Latif; Herwina, Wiwin; Laksono, Bayu Adi (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Abstract. This study examines the efforts of Community Self-Help Activators (PSM) in increasing community participation through the Bulan Bhakti Gotong Royong Masyarakat (BBGRM) activities in Ciamis Regency. This research uses a qualitative method with a descriptive approach to describe the strategies and methods used by PSM in educating, training, and assisting the community and village apparatus. The results show that PSM's role is crucial in enhancing active community participation through counseling, training, and assistance. Innovations such as using Zoom application for counseling have proven effective in quickly and widely disseminating information. Challenges such as limited internet access and technological skills among the community are addressed by providing technical guidance. Technical Guidance Training (Bimtek) also helps improve the community's understanding and skills in implementing BBGRM. Overall, PSM's efforts in increasing community participation through BBGRM activities in Ciamis Regency have successfully raised awareness, involvement, and contributions from the community.